Ultrasound findings in prediction of breast cancer histological grade and HER2 status - Mohson, Khaleel I. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Breast cancer is the most frequent cancerous tumor and major cause of death from cancer between women all over the world.Objectives: is to assess if ultrasound features of breast cancer can predict its histopathological grade and HER2 status of breast cancer for patients had their diagnosis in Oncology Teaching Hospital in Medical city complex from September 2014 to November 2015Patients and Methods: This is retrospective study of 102 patients whom histopathologically proved breast cancer had reviewed their ultrasound findings and correlate them with histopathological grade and HER2 status.Results: well circumscribed lesions, poorly defined and spiculated lesions are more likely to be of intermediate to high grade histopathology with negative HRE2 status while malignant LNs states are more likely to be from moderate to high grade with positive HER2.Conclusion: Breast ultrasound is a good tool in prediction of histopathology and HER2 status by assessment breast lesion morphology, outline and margin